(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article examines the importance of taxes in the state economy, and it is based on the fact that reducing bad tax debt is one of the most urgent issues in the country today. Opinions and opinions of foreign economists on reducing bad tax debt were studied. Tax debts of legal entities, including individual entrepreneurs, were analyzed. The characteristics of bad tax debt write-offs have been studied in developed countries. Based on the above-mentioned circumstances, proposals and recommendations have been formulated to reduce tax debt in our country, including improving the practice of its effective collection.